Association of Oxidative Stress, Iron, and Centralized Fat Mass in Healthy Postmenopausal Women - Crist, Betsy L. (Mary Ann Liebert, Inc., 2009)
OBJECTIVE: Centralized adiposity, insulin resistance, excess iron, and elevated oxidative stress place postmenopausal women at risk for atherosclerotic cardiovascular disease (CVD). The objective of this study was to determine the relationship among excess iron, oxidative stress, and centralized fat mass in healthy postmenopausal women. METHODS: The parent project recruited healthy women for a randomized, double-blind, clinical trial designed to examine the effect of soy isoflavones on bone. At baseline (n = 122), we measured three antioxidant enzymes, iron status indices (serum ferritin among others), oxidative stress indices (oxidized low-density lipoprotein [oxLDL], urinary isoprostanes [PGF(2α)], protein carbonyls, DNA damage), and waist, hip, and thigh fat mass using dual-energy x-ray absorptiometry (DXA). We calculated insulin resistance using the homeostasis model assessment (HOMA). Multiple regression analysis was used to determine the CVD risk factors that contributed to oxidative stress and centralized fat mass (waist + hip/thigh = AndGynFM ratio). RESULTS: Almost 14% (p < 0.0005) of the variability in oxLDL was accounted for by AndGynFM ratio (6.1%, p < 0.0005), age (4.0%, p = 0.012), and serum iron (2.8%, p = 0.053). Similarly, 16% (p < 0.0001) of the variability in PGF(2α) was accounted for by the AndGynFM ratio (4.8%, p = 0.011), HOMA (3.9%, p = 0.021), and serum iron (2.7%, p = 0.054). We accounted for 33% (p ≤ 0.0001) of the variability in AndGynFM ratio by high-density lipoprotein cholesterol (HDL-C) (4.3%, p = 0.008), ferritin (4.9%, p = 0.005), HOMA (4.5%, p = 0.006), oxLDL (2.6%, p = 0.04), and PGF(2α) (3.0%, p = 0.025). CONCLUSIONS: Our study suggests that reducing centralized fat mass and maintaining a favorable lipid profile, antioxidant status, and iron status all may be important in protecting postmenopausal women from atherosclerotic CVD.